ONE YEAR EXPERIENCE WITH INCLISIRAN IN AN ACADEMIC LIPID CLINIC: - Tommy T. Chiou, BA; Kimberly Tomasi, RN, BSN; Pam R. Taub, MD; Michael J. Wilkinson, MD (Elsevier, 2023)
Therapeutic Area: Pharmacologic Therapy Background: Real-world data examining inclisiran use in US clinical practice are limited. We report a one-year experience with inclisiran in an academic lipid clinic. Methods: Retrospective chart review of patients prescribed inclisiran since FDA approval in December 2021. Results: 80 patients were prescribed inclisiran over 14 months (Table). Inclisiran was approved by insurance for 70 (88%) and denied for 10 (12%). 48 (60%) could not tolerate any statin as background lipid-lowering therapy (LLT). All patients with Medicare received approval for inclisiran, compared to 12 of 22 (55%) of non-Medicare patients. Approved patients were older (71±8 vs 59±15 years, p=0.004), disproportionately Medicare enrollees (83%, p<0.001), more had ASCVD (69% vs 31%, p=0.031), less had HeFH (20% vs 80%, p=0.013), and fewer were on statins as background LLT (33% vs 67%, p=0.035).61 of 70 (87%) patients with approval have received at least one dose of inclisiran (19 received one dose, 37 received two, 5 have received three). 3 (5%) reported side-effects (1 injection site pain, 1 fever, 1 paresthesia and swelling in extremity leading to discontinuation).Using most recent LDL-C measured at least 30 days after first dose of inclisiran (n=38, 6 received one dose, 27 received two, 5 have received three), mean LDL-C decreased from 121±56 mg/dL to 85±55 mg/dL (-21%, p=0.003). Among the 25 patients who did not switch from a PCSK9i mAb (n=9) or stop their background LLT (n=5), LDL-C decreased from 139±44 mg/dL to 72±30 mg/dL (-49%, p<0.001) (Figure). LDL-C reduction differed by background PCSK9i mAb use (p<0.001) and discontinuation of background LLT (p=0.003), but not by sex, history of ASCVD or HeFH, background statin use, or number of inclisiran injections received. Conclusions: During the initial 14 months of prescribing inclisiran, 100% of patients on Medicare obtained insurance approval compared to roughly half of those with non-Medicare insurance who were younger and more likely to have HeFH. Among patients who had follow-up LDL-C, did not discontinue background LLT, and were not transitioning to inclisiran from a PCSK9i mAb, we observed LDL-C reductions of ∼50% which is similar in magnitude to those observed in clinical trials with inclisiran.